Edukasi Hidup Sehat Untuk Mengatasi Masalah Kesehatan Remaja - Syuja, Najmie Muhammad; Permana, Mohammad Rafli; Putri, Andhini Eka; Rifqiyah, Iffatur; Ziv, Khansa Fikriyah; Sukoco, Naura Hasyifa Anindya; Zakwan, Hazy Rizali; Affan, Muhammad; Rahayu, Safira Sri; ‘Azhim, Muhammad Fauzan; Widayati, Aris (Universitas Muhammadiyah Yogyakarta, 2025)
Community service is a form of implementation of the Tri Dharma of Higher Education, which emphasizes community service. Community service can be carried out in various forms of activities and assistance. The community service program carried out in Kalidadap 1 Hamlet, Selopamioro Village, Imogiri District, Bantul focuses on empowering adolescent health. The observation results show problems related to the lack of attention to adolescent health. Therefore, the purpose of this program is to increase the knowledge and awareness of adolescents in Kalidadap 1 Hamlet, so that they can foster an attitude of concern for their health. The method used in this activity is an educational approach that includes a series of integrated activities, namely counseling on reproductive health, balanced nutrition, prevention of anemia, training of adolescent health cadres, family care, and counseling on Clean and Healthy Living Behavior (PHBS). Community service is a form of implementation of Tri Dharma Perguruan. The results of the implemented program showed an increase in knowledge, skills, and awareness of adolescents towards health through education on anemia prevention, the dangers of promiscuity, the importance of balanced nutrition, and reproductive health. In addition, this activity also had a positive impact on improving the skills of health cadres in measuring hemoglobin and providing education on anemia prevention. Thus, this service program is expected to have a positive impact in the long term and can help the community in creating a healthier, smarter, more productive, and competitive younger generation in Kalidadap 1 Hamlet.